2016
DOI: 10.1177/0956462416630674
|View full text |Cite
|
Sign up to set email alerts
|

HIV self-testing in Peru: questionable availability, high acceptability but potential low linkage to care among men who have sex with men and transgender women

Abstract: HIV status awareness is key to prevention, linkage-to-care and treatment. Our study evaluated the accessibility and potential willingness of HIV self-testing among men who have sex with men (MSM) and transgender women in Peru. We surveyed four pharmacy chains in Peru to ascertain the commercial availability of the oral HIV self-test. The pharmacies surveyed confirmed that HIV self-test kits were available; however, those available were not intended for individual use, but for clinician use. We interviewed 147 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 10 publications
(13 reference statements)
6
36
0
2
Order By: Relevance
“…Interview data provided rationale for why STI clinic patients might be willing to deliver HIVST kits to their partners with PDPT, which could help facilitate disruption of STI and HIV transmission if implemented with favorable uptake. This data supports a growing body of evidence supporting the acceptability of HIVST (Ahmed-Little et al, 2016; Bavinton et al, 2013; Bustamante et al, 2017; Choko et al, 2015; Gaydos et al, 2011; Kelvin et al, 2016; Kurth et al, 2016; Lee, Brooks, Bolan, & Flynn, 2013; Pal et al, 2016; Prestage et al, 2016; Witzel, Rodger, Burns, Rhodes, & Weatherburn, 2016). Moreover, this research adds to prior data on the acceptability of secondary distribution of HIVST kits to sexual partners (Kalibala et al, 2014; Lippman et al, 2016; Masters et al, 2016; Prestage et al, 2016; Thirumurthy et al, 2016), indicating rationale for why individuals might find it acceptable.…”
Section: Discussionsupporting
confidence: 82%
“…Interview data provided rationale for why STI clinic patients might be willing to deliver HIVST kits to their partners with PDPT, which could help facilitate disruption of STI and HIV transmission if implemented with favorable uptake. This data supports a growing body of evidence supporting the acceptability of HIVST (Ahmed-Little et al, 2016; Bavinton et al, 2013; Bustamante et al, 2017; Choko et al, 2015; Gaydos et al, 2011; Kelvin et al, 2016; Kurth et al, 2016; Lee, Brooks, Bolan, & Flynn, 2013; Pal et al, 2016; Prestage et al, 2016; Witzel, Rodger, Burns, Rhodes, & Weatherburn, 2016). Moreover, this research adds to prior data on the acceptability of secondary distribution of HIVST kits to sexual partners (Kalibala et al, 2014; Lippman et al, 2016; Masters et al, 2016; Prestage et al, 2016; Thirumurthy et al, 2016), indicating rationale for why individuals might find it acceptable.…”
Section: Discussionsupporting
confidence: 82%
“…There is a growing body of literature that suggests that HIV self-testing, administered in a location of an individual's choosing, is acceptable to transgender women and may address concerns with privacy, confidentiality, and stigma (HIV-related, transgender) often encountered by transgender women in the context of clinic-based HIV testing. [42][43][44] However, in the absence of structural interventions to address stigma in healthcare settings, transgender women living with HIV may continue to experience barriers accessing the HIV care continuum. 42 HIV positive participants were 6-fold more likely to be homeless, and a history of incarceration was associated with substantially (>70%) reduced odds of ever receiving an HIV test.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the feasibility and acceptability of HIVST among MSM and TW has predominantly originated from Europe and the U.S., where self-testing has been approved and available over-the-counter since 2012 [11]. Some studies have recently been reported from the Latin American and sub-Saharan African regions, as well as China and Cambodia [18][19][20]. A review on the acceptability and feasibility of self-testing among key populations has found general acceptance of HIVST among MSM, particularly noting convenience and privacy of testing [18].…”
Section: Introductionmentioning
confidence: 99%